Experimental Study on Uniaxial Compressive Strength of Concrete Incorporated with Cigarette Butts. Issue 5 (February 2019) - Luo, Tao; Zhang, Zhaojing; Zhang, Jinliang; Sun, Chaowei; Yanjun, JI
Abstract: Mixing cigarette butts into concrete to reduce the urban heat island effect caused by concrete while dealing with cigarette butts waste, the possibility of "one stone catches two birds" provides a new idea for urban environmental protection. The influence of cigarette butts content on the mechanical properties of concrete needs to be studied. The cigarette butts are cleaned and dried, then sealed and hardened by paraffin wax. Cigarette butts are mixed into concrete cubic block according to the content of 0kg/m 3, 5kg/m 3, 7.5kg/m 3, 10kg/m 3, 12.5kg/m 3, 15kg/m 3 and 20kg/m 3 respectively. The cubic uniaxial compression test is carried out. With the increase of cigarette butts content, the concrete strength decreased continuously, if the cigarette content is not exceed 10kg/m 3, the reduction of strength is slow, and the maximum strength loss is 13%. If the cigarette content is larger than 10kg/m 3, the strength reduces faster, when the cigarette butt content achieves 20kg/m 3, the strength loses 30%. For the concrete with no cigarette, it crushes into many pieces, with the increase of content of cigarette butts, the failure pattern shows better ductility.